Is congruent movement training more effective than standard visual scanning therapy to ameliorate symptoms of visuospatial neglect? Study protocol of a randomised control trial - Tanja C W Nijboer; Joris A Elshout; Stefan Van der Stigchel (BMJ Open)
Introduction Approximately 30% of all patients with stroke show visuospatial neglect (VSN). Currently, visual scanning therapy (VST) is applied in clinical settings to attenuate neglect symptoms. VST builds on the premise that eye movements to the affected hemifield lead to a concurrent shift of visual attention. Congruent movements with different effectors of the motor system, for example, eye and hand, can produce an even larger boost of attention compared with a single effector. This congruency principle may produce a powerful bias in the motor system, which may counteract the pathological biases in the attentional system of neglect patients. Therefore, an intervention with congruent eye and hand movements may result in greater attenuation of neglect compared with an intervention with single eye movements as applied in standard VST. The current randomised controlled trial will investigate the beneficial effects of this updated version of VST by comparing changes in performance on standard neuropsychological neglect tasks and severity of neglect in activities of daily living.Methods and analysis Thirty VSN patients in the subacute phase poststroke onset will be randomly assigned to one of two groups: congruent eye and hand movement training (experimental group) versus standard VST (control group). Each patient will receive 10 sessions of training, 30 min each, within 2 weeks. Performance on standard neuropsychological neglect tasks, a visual discrimination task, severity of neglect in ADL and eye movement characteristics before and after intervention will be compared for and between both groups.Ethics and dissemination This study has been approved by the ethical committee of the University Medical Centre Utrecht. All subjects will participate voluntarily and will give written informed consent. Results of this study will be published in peer-reviewed scientific journals and presented at international conferences.Trial registration number NTR7005